2006
DOI: 10.3846/16111699.2006.9636115
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Cost Analysis: Actual Problem in Industrial Management

Abstract: The reliability associated costs are the main part of total life cycle cost for any repairable system. The paper presents the history of life cycle cost analysis, its principles and applicable standards. It analyzes the reasons behind the contradiction between the great theoretical achievements and their relatively rare applications in practice. It was shown that incorrect management is the main reason. Measures for management improvement were suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…During the lifecycle of expensive capital goods, different cost factors must be considered. Elmakis and Lisnianski (2006) differentiate between following cost categories: development costs, production costs, operation and service costs, and disposal costs. In this section, we describe how consolidation with AM may change these cost categories and explain how these changes are regarded in our model.…”
Section: Effects Of Consolidation On Lifecycle Costsmentioning
confidence: 99%
“…During the lifecycle of expensive capital goods, different cost factors must be considered. Elmakis and Lisnianski (2006) differentiate between following cost categories: development costs, production costs, operation and service costs, and disposal costs. In this section, we describe how consolidation with AM may change these cost categories and explain how these changes are regarded in our model.…”
Section: Effects Of Consolidation On Lifecycle Costsmentioning
confidence: 99%
“…Life Cycle Costs are described as "cradle-to-grave" costs summarized as an economic model of evaluating alternatives for equipment and projects [8]. [9] defined LCC as the total cost of acquiring and utilizing a system over its entire life span, in other words LCC is the total cost of procurement and ownership. More detailed definitions are proposed by [10] -Life cycle cost is the total cost of ownership of machinery and equipment, including its cost of acquisition, operation, maintenance, conversion, and/or decommission -and [11] -LCC are summations of cost estimates from inception to disposal for both equipment and projects as determined by an analytical study and estimate of total costs experienced in annual time increments during the project life with consideration for the time value of money.…”
Section: State Of the Artmentioning
confidence: 99%
“…Schematically, the PLC can be approximated by a bell-shaped curve that is divided into several stages. The PLC is typically depicted as a unit sales curve of a product category over time [7][8][9][10][11][12][13][14][15][16]. Another important issue faced by firms is the vendor selection (VS) problem.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of PLC cost (PLCC) originates from the US Department of Defense and is focused on a product's entire value chain from a cost perspective since the development phase of a product's life, through design, manufacturing, marketing/distribution and finally customer services [8]. Elmark and Anatoly (2006) indicated that the PLCC is the total cost of acquiring and utilizing a system over its complete life span [10]. Vasconcellos and Yoshimura (1999) proposed a breakdown structure to identify the main activities for the active life cycle of automated systems [11].…”
Section: Introductionmentioning
confidence: 99%